Efektifitas Core Stability Exercise Dengan Metode Bobath Terhadap Keseimbangan Pada Pasien Pasca Stroke - Satya Liwa Marliando; Wahyu Tri Sudaryanto (LPPM STIKES Siti Hajar dan Insight Power, 2022)
Stroke is a disease of cerebral blood circulation which is influenced by many dangerous factors. Post-stroke conditions can interfere with daily activities due to impaired nerve function that affects muscle strength, body balance, and other body functions. The function of balance is to protect the body from gravity and other external factors. In the movement process, postural muscle tone has a significant impact on the effectiveness and efficiency of the resulting motion. It is hoped that core stability exercise with the bobath concept would reactivate the postural muscles also improve patient's posture and balance. The purpose of this study is to determine the effectiveness of core stability exercise with the concept of bobath on balance ability in post-stroke patients. The sample of the research was Mr. B is 49 years old with non hemorrhagic post-stroke patients with right hemiparase motor disorders. Impaired balance when standing and walking with asymmetrical posture. After the evaluation, it was found that the score changes from T0 to T6, starting from T0 getting a score of 41, T3 getting a score of 44, and T6 getting a maximum score of 47. An increase in the first evaluation score to the last evaluation score can be observed. Based on the research that has been done, core stability using the bobath method is effective in improving the ability to balance post-stroke with right hemiparase. Keywords: Stroke, Non-Hemoragik, Core Stability Exercise, Bobath